2020
DOI: 10.2147/jmdh.s255781
|View full text |Cite
|
Sign up to set email alerts
|

<p>Investigating Stress and Sources of Stress Among Female Health Profession Students in a Saudi University</p>

Abstract: Background: Health profession students experience tremendous levels of stress throughout their education. A high level of stress may have a negative effect on the cognitive functioning and learning of students. Objective: The study sought to determine the levels and main sources of stress and its possible correlation with academic performance in the preclinical female health profession. Methods: The cross-sectional design involved the use of self-administered questionnaires. Data were collected from 260 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Numerous worldwide studies were conducted to assess the level of perceived stress among University students before the COVID-19 pandemic (Shah et al, 2010 ; Borjalilu et al, 2015 ; Ahmed and Prashantha, 2018 ; Gazzaz et al, 2018 ; Al-Qahtani and Alsubaie, 2020 ; Karyotaki et al, 2020 ; Tariq et al, 2020 ), but only limited studies were conducted on the same issue during the COVID-19 outbreak. The available studies reported a high perceived stress level for students ranging from 12.6 to 30.2% during the current pandemic (AlAteeq et al, 2020 ; Pedrozo-Pupo et al, 2020 ; Sheroun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous worldwide studies were conducted to assess the level of perceived stress among University students before the COVID-19 pandemic (Shah et al, 2010 ; Borjalilu et al, 2015 ; Ahmed and Prashantha, 2018 ; Gazzaz et al, 2018 ; Al-Qahtani and Alsubaie, 2020 ; Karyotaki et al, 2020 ; Tariq et al, 2020 ), but only limited studies were conducted on the same issue during the COVID-19 outbreak. The available studies reported a high perceived stress level for students ranging from 12.6 to 30.2% during the current pandemic (AlAteeq et al, 2020 ; Pedrozo-Pupo et al, 2020 ; Sheroun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…El estrés en los estudiantes de enfermería se ha intensificado durante la pandemia de COVID-19 por la naturaleza de su formación, porque deben enfrentarse a las actividades académicas y a la percepción del riesgo de contagio simultáneamente (26). Debido a que, además de que se están formando como profesionales deben interiorizar que pertenecen a una profesión de servicio, de responsabilidad social y de valores éticos, para salvaguardar la salud y la vida de sus conciudadanos (27).…”
Section: Resultsunclassified
“…Kadapatti and Vijayalaxmi (2012) [12] indicated that high aspiration level, poor study habits, change in medium of instructions and low socioeconomic status were the major stressors of academic stress among pre-university students. Al-Qahtani and Alsubaie (1920) [3] found that academic and group activity domains were perceived as the major stressors among health profession students. Dickson et al, (2020) [6] conducted a study and found that stress comes from academic tests, interpersonal relations, relationship problems, life changes, and career exploration.…”
Section: Review Of Literaturementioning
confidence: 99%